Addressing Participant Inattention in Federal Programs: A Field Experiment with the Conservation Reserve Program. (19th April 2017) - Wallander, Steven; Ferraro, Paul; Higgins, Nathaniel
Abstract: Voluntary land conservation programs depend upon the willingness of land owners to participate. Since participation requires commitment to long‐term contracts, most studies on participation focus on changes to the pecuniary incentives facing land owners. This study presents a large‐scale field experiment within the USDA's Conservation Reserve Program (CRP) that examines whether informational outreach, including behavioral nudges, could improve land owners' willingness to participate. The experiment evaluates the impact of three types of reminder letters on the rate at which land is offered into the CRP. We find that for the most well‐informed group, farms with expiring CRP contracts, the reminder letters did improve participation. We interpret this result as evidence of inattentive behavior. We do not detect any differences in the estimated treatment effects among the basic reminder letter and the letters augmented with peer comparisons and social norm messaging, nor do we detect any treatment effect among currently unenrolled farms. From a policy perspective, these results imply that the USDA can generate additional CRP offers among farms with expiring contracts at an average cost of $39 per additional offer. Assuming a twenty‐five million acre program, reminder letters sent during every sign‐up period would result in re‐enrollment offers from an additional 420, 000 acres. Using simulations based on offers from prior CRP sign‐ups, we estimate that these additional offers in the CRP auction would reduce program costs. Depending on the year of simulation, the outreach effort achieves a benefit‐cost ratio of between 20:1 and 90:1.